2021
DOI: 10.3390/ma14143996
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Adsorbents from Spent Coffee for Removal of Methylene Blue and Methyl Orange from Water

Abstract: Activated carbons (ACs) were prepared from dried spent coffee (SCD), a biological waste product, to produce adsorbents for methylene blue (MB) and methyl orange (MO) from aqueous solution. Pre-pyrolysis activation of SCD was achieved via treatment of the SCD with aqueous sodium hydroxide solutions at 90 °C. Pyrolysis of the pretreated SCD at 500 °C for 1 h produced powders with typical characteristics of AC suitable and effective for dye adsorption. As an alternative to the rather harsh base treatment, calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 47 publications
(74 reference statements)
2
25
0
Order By: Relevance
“…Those weight losses were reported to be a thermal decomposition of the amorphous cellulose regions and oxidation of the carbon skeleton [55]. Similar thermogravimetric curves were previously reported from materials with hemicellulose and lignin content [53,56,57]. Weight losses of 98% in the range from 445 • C to 546 • C, and of 93% from 504 • C to 601 • C, were reported for spent coffee grounds and parchment activated carbons, respectively.…”
Section: Characterization Of the Activated Carbon Materialssupporting
confidence: 81%
“…Those weight losses were reported to be a thermal decomposition of the amorphous cellulose regions and oxidation of the carbon skeleton [55]. Similar thermogravimetric curves were previously reported from materials with hemicellulose and lignin content [53,56,57]. Weight losses of 98% in the range from 445 • C to 546 • C, and of 93% from 504 • C to 601 • C, were reported for spent coffee grounds and parchment activated carbons, respectively.…”
Section: Characterization Of the Activated Carbon Materialssupporting
confidence: 81%
“…This is because the lignin content has a value on the order of spent coffee > biochar. Consequently, the study indicated that the higher the lignin level, the greater the carbon content [ 27 ]. Because of the high carbon and low ash content, the spent coffee was found to be appropriate for the preparation of carbon black.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the heavy metal ions' adsorption equilibrium on carbonaceous materials, the Langmuir isotherm, Equation (5), and the Freundlich isotherm, Equation (6) [20][21][22][23], were applied. The Langmuir model is expressed as follows [20]:…”
Section: Data Evaluationmentioning
confidence: 99%
“…Thanks to the above properties, activated carbons have been successfully used for the removal of pollutants from water and air; for separation of gas mixtures; and for recovery of valuable substances, e.g., gold or silver. Adsorption on activated carbons has been applied in many sectors of the economy in a wide range of processes from food, pharmaceutical, and petrochemical industries to purification of drinking water, post-industrial wastewater, municipal wastewater, and exhaust gases [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%